Non-selective beta-blockers and the incidence of hepatocellular carcinoma in patients with cirrhosis: a meta-analysis - He, Xinyi; Zhao, Zimo; Jiang, Xi; Sun, Yan (Frontiers in Pharmacology, 2023)
Background: Hepatocellular carcinoma (HCC) is a serious complication of cirrhosis. Currently, non-selective beta-blockers (NSBBs) are commonly used to treat portal hypertension in patients with cirrhosis. The latest research shows that NSBBs can induce apoptosis and S-phase arrest in liver cancer cells and inhibit the development of hepatic vascular endothelial cells, which may be effective in preventing HCC in cirrhosis patients. Aim: To determine the relationship between different NSBBs and HCC incidence in patients with cirrhosis. Methods: We searched the Cochrane database, MEDLINE, EMBASE, PubMed, and Web of Science. Cohort studies, case‒control studies, and randomized controlled trials were included if they involved cirrhosis patients who were divided into an experimental group using NSBBs and a control group with any intervention. Based on heterogeneity, we calculated odds ratio (OR) and 95% confidence interval (CI) using random-effect models. We also conducted subgroup analysis to explore the source of heterogeneity. Sensitivity analysis and publication bias detection were performed. Results: A total of 47 studies included 38 reporting HCC incidence, 26 reporting HCC-related mortality, and 39 reporting overall mortality. The HCC incidence between the experimental group and the control group was OR = 0.87 (0.69 and 1.10), p = 0.000, and I2 = 81.8%. There was no significant association between propranolol (OR = 0.94 and 95%CI 0.62–1.44) or timolol (OR = 1.32 and 95%CI 0.44–3.95) and HCC incidence, while the risk of HCC decreased by 26% and 38% with nadolol (OR = 0.74 and 95%CI 0.64–0.86) and carvedilol (OR = 0.62 and 95%CI 0.52–0.74), respectively. Conclusion: Different types of NSBB have different effects on the incidence of patients with cirrhosis of the liver, where nadolol and carvedilol can reduce the risk. Also, the effect of NSBBs may vary in ethnicity. Propranolol can reduce HCC incidence in Europe and America. Systematic Review Registration: identifier https://CRD42023434175, https://www.crd.york.ac.uk/PROSPERO/.